DI-051 Development of lay descriptions of diabetes related complications for patient education in taiwan. (25th February 2017) - Lin, YJ; Ko, Y; Wang, CY; Chang, EH; Cheng, SW
Abstract : Background: Patient education is a key determinant of clinical outcomes in diabetes care. Concise and accurate descriptions of diabetes related complications that could be easily understood by patients are essential to successful patient education. Furthermore, descriptions could be used in utility/preference assessments to obtain important data for pharmacoeconomic research. Purpose: To develop descriptions of common diabetes related complications that patients with diabetes in Taiwan could understand and apply. Material and methods: This was a qualitative study that included interviews with diabetes health professionals and patient focus groups. 11 diabetes related complications were selected based on a literature review of recent pharmacoeconomic studies of oral diabetic agents. A description for each complication was drafted based on information collected from medical books, websites and literature searches. To then improve upon these descriptions, 2 physicians and 5 diabetes educators were interviewed individually. Each of the 7 health professionals had more than 12 years of experience in diabetes care. In addition, two focus group interviews involving a total of 8 patients with diabetes were conducted; each patient had actually experienced at least 1 of the 11 complications examined. Results: Our initial descriptions consisted of information such as levels of mobility, pain, emotions, treatments needed and usual activities affected. Modifications were made after the interviews; for example, health professionals corrected the follow-up intervals from 6 months or annually to 3 months based on actual practice in Taiwan. In addition, it was found that diabetes educators provided more comments on emotional aspects (eg, fear and anxiety) of the complications whereas the physicians focused more on the symptoms and discomfort. During the focus group interviews, patients shared their personal experiences and helped identify difficult medical terms or statements that could be modified to make the descriptions more comprehensible to the general public. The final descriptions contained 4–8 sentences for each complication. Conclusion: In this study, we developed descriptions of 11 diabetes related complications by patient and health professional interviews. These descriptions could be useful for diabetes patient education and utility/preference measurement. References and/or acknowledgements: This study was sponsored by the Shin Kong Wu Ho-Su Memorial Hospital (SKH-8302-105-NDR04) and AstraZeneca Taiwan Ltd (A-104-062). Conflict of interest: Corporate sponsored research or other substantive relationships: This study was sponsored by the Shin Kong Wu Ho-Su Memorial Hospital (SKH-8302-105-NDR04) and AstraZeneca Taiwan Ltd (A-104-062).